Compelling Evidence for a Harmonic in the Light Curve of the Supermassive Black Hole Binary Candidate PKS J1309+1154 - Readhead, A. C. S.; Aller, M. F.; Sullivan, A. G.; Blandford, R. D.; Mróz, P.; De La Parra, P. V.; Molina, B.; Most, E. R.; Lister, M. L.; Synani, A.; Aller, H.; Begelman, M. C.; et al. (Institute of Physics Publishing, 2026)
We recently discovered a supermassive black hole binary (SMBHB) candidate, PKS J1309+1154, in the combined 46 yr University of Michigan Radio Astronomy Observatory (UMRAO) plus Owens Valley Radio Observatory (OVRO) blazar monitoring programs at 14.5/15 GHz. The light curve of PKS 1309+1154 exhibits a 17.9 yr periodicity. We also reported a hint of a first harmonic with a 9 yr periodicity in this object. Further analysis of the PKS J1309+1154 light curve provides compelling evidence that both the fundamental and the harmonic are real, confirming the existence of real periodicities in blazar light curves. This is the first case, to our knowledge, of watertight evidence for a fundamental periodicity and a harmonic periodicity in a blazar light curve. It makes PKS J1309+1154 a strong SMBHB candidate and thus the third such candidate to be revealed through long-term radio monitoring, the other two being PKS J0805–0111 and PKS 2131–021, both discovered through the OVRO 40 m Telescope monitoring program. It is argued that hundreds of SMBHB candidates will be discovered by the combination of the South Pole Telescope, the Vera Rubin Observatory, and the Simons Observatory. Coherent searches for gravitational waves from a network of SMBHB candidates, starting immediately, are strongly motivated.